Molecular drivers of oral cavity squamous cell carcinoma in non-smoking and non-drinking patients: what do we know so far? - Sophia Uddin; Alka Singh; Vasudha Mishra; Nishant Agrawal; Zhen Gooi; Evgeny Izumchenko (Frontiers Media S.A., 2022)
Oral cavity squamous cell carcinoma (OCSCC) is one of the most common head and neck cancers worldwide. It is well known that risk factors for OCSCC include tobacco and excess alcohol consumption. However, in recent years, OCSCC incidence has been increasing in patients without these traditional risk factors. The cause of this increase is unclear and various genetic, environmental, and infectious factors have been hypothesized to play a role. Additionally, there are expert opinions that oral cancer in non-smoking, non-drinking (NSND) patients have a distinct phenotype resulting in more aggressive disease presentation and poorer prognosis. In this review, we summarize the current state of knowledge for oral cavity cancer in patients without traditional risk factors.